061 Guideline Implementability Appraisal (GLIA) in US National Guidelines. (15th August 2013) - Chan, W; Pearson, T
Abstract : Background: Guidelines must be implemented in order to impact health outcomes. Identifying and addressing potential barriers to implementation during guideline development can improve implementability. Objectives: To describe the processes and results of embedding guideline implementability appraisal, into prominent US cardiovascular disease risk reduction guidelines. Methods: The GuideLine Implementability Appraisal (GLIA) tool (Yale Center for Medical Informatics), was integrated into the guideline development processes of a US national-level organisation. A member of the Implementation Science Work Group (ISWG) with prior experience in GLIA appraisals trained the Guideline Development Teams (GDTs), early in the guideline development process, with the intent of raising awareness of potential barriers to implementation so they might be addressed during guideline development. Formal GLIA appraisals were performed on the drafts of the guideline reports, by members of the ISWG, as well as volunteers from outside the guideline programme. To minimise interference with timelines, appraisals were carried out and written reports returned to the GDTs within 2 weeks of release of the draft reports. Results: A number of potential barriers to implementation were identified in the draft reports, such as: use of inexplicit terms in recommendation language, inconsistency of thresholds and terms used within a guideline, unclear applicability of assessment or treatment recommendations in specific subgroups. GDTs considered GLIA appraisal findings when they revised their reports and found the GLIA appraisals helpful in creating more implementable guidelines. Implications for Guideline Developers/Users: GLIA training for GDTs, and formal use of the GLIA tool help produce more implementable guidelines.